Early Home Therapies against Covid-19. An Italian Case of Politicisation of Science? - Campo, Enrico; De Toffoli, Matteo; Gobo, Giampietro; Strata, Fabrizio (PARTECIPAZIONE E CONFLITTO, 2023)
Since February 2020, strategies aimed at containing and managing the Covid-19 syndemic have been developed by the governments of European countries. Among these measures, the possibility of an early treatment of the disease has been considered of fundamental importance, both for curing the disease and governing the syndemic. Despite their potential, early therapies received a somehow unexpected treatment in Italy and the debate around them gave rise to a very evident conflict between proponents and opponents of those treatments, to the point that some of the former organised a properly political movement in order to promote the integration of early home therapies in the official health protocols. Not surprisingly, the issue of early therapies has been considered an exemplary case of politicisation of science. However, the assimilation of the early therapy controversy to the frame of politicisation of science cannot fully explain why these protocols were discarded by political and health authorities. Rather, the consideration of health protocols as socio-technical objects shifts the attention on the vast range of cultural, political and economic factors that contributed to the general resistance towards those treatments. Therefore, we aim to analyse the media coverage of the phenomenon, and investigate the protocols of home treatment of Covid-19, paying attention to the interaction of the factors that contributed to the exclusion of home therapies into national guidelines.